2021
DOI: 10.2174/2211352518999200729111045
|View full text |Cite
|
Sign up to set email alerts
|

Biological Evaluation of Synthesized Naringenin Derivatives as Antimicrobial Agents

Abstract: Flavonoids are among the most abundant plant secondary metabolites and have been shown to have natural abilities as microbial deterrents and anti-infection agents in plants. Naringenin as one of the flavonoids and its derivatives have been reported to exhibit antimicrobial activity. The aim of the study was to evaluate synthesized novel naringenin derivatives (ND-1 to ND-12) substituted at 3-position with bulky substituent by using the grinding technique (Claisen-Schmidt reaction) as antimicrobial agents. Synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Results of naringin were significantly worse comparing to naringenin. Some close derivatives of naringenin tested by Murti et al and Duda-Madej et al had surprisingly satisfying values (MIC ≤ 50 µg/mL) shown in the Scheme 2 a,b [ 67 , 80 ]. Beside in vitro measurements of MICs, there are a number of molecular and biochemical studies demonstrating the effect of this bioflavonoid on the Gram-negative bacterial cell.…”
Section: Antimicrobial Activity Against Gram-negative Bacteriamentioning
confidence: 99%
See 2 more Smart Citations
“…Results of naringin were significantly worse comparing to naringenin. Some close derivatives of naringenin tested by Murti et al and Duda-Madej et al had surprisingly satisfying values (MIC ≤ 50 µg/mL) shown in the Scheme 2 a,b [ 67 , 80 ]. Beside in vitro measurements of MICs, there are a number of molecular and biochemical studies demonstrating the effect of this bioflavonoid on the Gram-negative bacterial cell.…”
Section: Antimicrobial Activity Against Gram-negative Bacteriamentioning
confidence: 99%
“…Although all of the derivatives showed antifungal activity, there are also moieties that may reduce it. The methoxy-substituted phenyl ring decreased the antifungal effect of naringenin [ 80 ]. According to the above-mentioned studies, different naringenin derivatives also have significant biological properties, some of them even greater than naringenin.…”
Section: Antifungal Activitymentioning
confidence: 99%
See 1 more Smart Citation